A biodegradable polyester composition and its preparation method and application

A biodegradable polyester composition with optimized polybutylene succinate, polylactic acid, and filler ratios stabilizes extrusion and enhances mechanical properties, addressing PBS/PLA blend instability and achieving consistent product thickness and heat resistance.

CN116285247BActive Publication Date: 2024-12-17KINGFA SCI & TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310203642.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-06
Publication Date
2024-12-17
Estimated Expiration
2043-03-06

AI Technical Summary

Technical Problem

Existing biodegradable PBS/PLA blends face issues with unstable extrusion during processing due to the properties of polybutylene succinate (PBS) and polylactic acid (PLA), leading to inconsistent product thickness and mechanical instability.

Method used

A biodegradable polyester composition comprising specific ratios of polybutylene succinate, polylactic acid, and filler, along with additives, is formulated and processed under controlled conditions to achieve stable extrusion and improved mechanical properties, with a thickness deviation of less than 2% and enhanced heat resistance.

Benefits of technology

The composition ensures stable extrusion with consistent product thickness and improved mechanical properties, including bending strength and heat resistance, by optimizing the interaction between polybutylene succinate, polylactic acid, and filler components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004109946710000031
    Figure BDA0004109946710000031
  • Figure BDA0004109946710000041
    Figure BDA0004109946710000041
  • Figure BDA0004109946710000051
    Figure BDA0004109946710000051
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer modification, and specifically relates to a biodegradable polyester composition, a preparation method thereof, and an application thereof. The biodegradable polyester composition comprises the following components in parts by weight: 35 to 55 parts of polybutylene succinate, 25 to 45 parts of polylactic acid, and 10 to 30 parts of filler; the melt flow rate of the polybutylene succinate under the test conditions of 190°C and 2.16kg is 2 to 8g / 10min; the residual monomer content of the polylactic acid is ≤0.3%; the D50 particle size of the filler is ≤10μm. The biodegradable polyester composition prepared by the present invention has a stable extrusion speed during the extrusion process, and the current is stable at a constant value during the extrusion process. The obtained straw product has a thickness range of <10μm and a relative thickness deviation of <2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer modification, and specifically relates to a biodegradable polyester composition and a preparation method and application thereof. Background Art

[0002] In recent years, my country has made breakthrough progress in the research and development of degradable plastics, and the level of industrialization has continued to improve. Driven by the accelerated construction of a green circular economy and the development of a sustainable economy in my country, and under the background of "carbon neutrality", my country's fully biodegradable plastics market has ushered in rapid growth.

[0003] As a raw material from natural sources, polylactic acid has mechanical properties very similar to those of PET and PS. It is a brittle and hard material and often cannot be used directly. The softening point of polylactic acid is 55°C. If used in an environment above 55°C, it will deform directly and cannot achieve the desired effect. Polybutylene glycol succinate (PBS) is a biodegradable material with a certain degree of crystallinity and good temperature resistance. The PBS material itself is a soft and tough material, so polylactic acid and PBS are often used for blending and modification in actual use. However, due to the properties of the PBS / PLA material itself, the two are prone to unstable extrusion during processing. Therefore, we continue to develop a PBS / PLA blend material that can be stably extruded. Summary of the invention

[0004] The present invention aims to provide a biodegradable polyester composition and a preparation method and application thereof. The biodegradable polyester composition prepared by the present invention has a stable extrusion speed during the extrusion process, a stable current during the extrusion process, and a thickness range of the prepared straw product is less than 10 μm and a relative thickness deviation is less than 2%.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a biodegradable polyester composition, comprising the following components in parts by weight: 35-55 parts of polybutylene succinate, 25-45 parts of polylactic acid, and 10-30 parts of filler;

[0006] The melt flow rate of the polybutylene succinate under the test conditions of 190° C. and 2.16 kg is 2 to 8 g / 10 min;

[0007] The residual monomer content of the polylactic acid is ≤0.3%;

[0008] The D50 particle size of the filler is ≤10 μm.

[0009] The melt flow rate of polybutylene succinate in the present invention is tested according to GB / T 3682.1-2018 standard.

[0010] The D50 particle size of the filler in the present invention is determined by referring to the method of GB / T 19077-2016 "Particle Size Distribution Laser Diffraction Method".

[0011] Preferably, the biodegradable polyester composition comprises the following components in parts by weight: 45-50 parts of polybutylene succinate, 30-40 parts of polylactic acid, and 15-20 parts of filler.

[0012] Preferably, the filler includes at least one of calcium carbonate, talcum powder, bamboo powder and straw powder.

[0013] Preferably, the D50 particle size of the filler is 0.5-10 μm.

[0014] Preferably, the straw made from the biodegradable polyester composition has a thickness range of <10 μm and a relative thickness deviation of <2%.

[0015] Preferably, the biodegradable polyester composition further comprises 0.2 to 2 parts of a processing aid.

[0016] Preferably, the processing aid includes at least one of a stabilizer, a lubricant, an antistatic agent, an antifogging agent, a UV absorber, and a UV stabilizer.

[0017] Preferably, the biodegradable polyester composition comprises at least one of the following (1) to (5):

[0018] (1) The stabilizer includes at least one of tribasic lead sulfate, dibasic lead stearate, lead stearate, calcium stearate, zinc stearate, magnesium stearate, etc.;

[0019] (2) The lubricant includes at least one of stearamide, oleamide, erucamide, zinc stearate, high molecular weight complex ester of metal soap, ethylene bisstearamide, polyethylene wax, and silicone lubricant;

[0020] (3) the antistatic agent comprises at least one of ethoxylated alkylamine, ethoxylated alkyl acid amine, and glyceryl monostearate (GMS);

[0021] (4) the anti-fogging agent comprises at least one of glycerol esters, polyglycerol esters, sorbitan esters, ethoxylated derivatives, ethoxylated nonylphenol, and ethoxylated alcohol;

[0022] (5) The UV absorber includes at least one of phenyl o-hydroxybenzoate, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.

[0023] A method for preparing the biodegradable polyester composition comprises the following steps:

[0024] The components are mixed uniformly, extruded and granulated at 150-240° C. to obtain a biodegradable polyester composition.

[0025] A use of the biodegradable polyester composition in manufacturing straws or extruded products.

[0026] The inventor found when studying the PBS / PLA blend system extrusion stability situation that the residual monomer content contained by the polylactic acid added has a significant impact on the melt strength of the composition in its processing, and when the residual monomer content of polylactic acid is higher, the melt strength of the composition declines more greatly in the processing. Therefore, among the present invention, by selecting the polylactic acid of specific melt flow rate polybutylene succinate and specific residual monomer content and the interaction between the filler of specific D50 particle diameter, the raising of the extrusion stability performance of the PBS / PLA blend system is realized. In addition, the adding of filler of the present invention can not only improve the appearance performance of the obtained product, but also can effectively improve the flexural strength and the heat resistance of biodegradable polyester composition.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The biodegradable polyester composition prepared by the present invention has a stable extrusion speed during the extrusion process, and the current is stable at a constant value during the extrusion process. The thickness range of the prepared straw product is less than 10 μm, the relative thickness deviation is less than 2%, and the product has good mechanical properties and heat resistance. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] In the following examples and comparative examples, the experimental methods used are conventional methods unless otherwise specified. Unless otherwise specified, the lubricants are commercially available and the same lubricants are used in parallel experiments.

[0031] The residual monomer content of polylactic acid in the present invention is tested as follows:

[0032] 1. Prepare standard solution

[0033] (1) Weigh 100±10 mg of pentamethylbenzene and mix it with 100 mL of dichloromethane solution. Shake well. This is called the internal standard solution.

[0034] (2) Weigh 100 ± 10 mg of L-lactide standard, prepare 100 mL of dichloromethane solution, shake well, and record it as the standard solution;

[0035] (3) Take 1.0, 2.0, 5.0, 10.0, and 20.0 mL of the standard solution and place them in 25 mL volumetric flasks. Add 4.0 mL of the internal standard solution to each flask, fill it up with n-hexane, and shake at a constant temperature. This is called the calibration standard solution.

[0036] 2. Sample testing

[0037] (1) Weigh 200±20 mg of polylactic acid sample (W) in a 20 ml glass vial, add 4.0 ml of internal standard solution, and dissolve the sample at room temperature. Stirring can be used to assist dissolution. After the sample is completely dissolved, slowly add 10 ml of n-hexane to the inner wall of the flask, stopper the vial, and then shake it vigorously for 5 to 10 seconds. Let the sample stand for 10 minutes;

[0038] (2) After filtering with a membrane filter, transfer to a dedicated injection vial for gas chromatography and perform the test according to the above-mentioned gas chromatography analysis conditions. Each sample solution should be injected at least 3 times.

[0039] 3. Calculation of residual monomer content of polylactic acid

[0040] Calculate the area ratio AR of lactide and pentamethylbenzene in the injected sample S and read the corresponding content ratio CR from the calibration curve S .

[0041] The lactide content of the sample during each GC run was calculated as follows:

[0042]

[0043] CR S : The content ratio read in the calibration curve;

[0044] IS S : The mass of pentamethylbenzene in 100mL of internal standard solution for sample determination [mg / 100mL];

[0045] W: weight of PLA sample weighed [mg].

[0046] The raw materials used in the examples and comparative examples are shown in Table 1.

[0047] Table 1

[0048]

[0049] Examples 1 to 10 and Comparative Examples 1 to 5

[0050] The components and weight proportions of the biodegradable polyester compositions of Examples 1 to 10 and Comparative Examples 1 to 5 are shown in Table 2.

[0051] The preparation method of the biodegradable polyester composition of Examples 1 to 10 and Comparative Examples 1 to 5 comprises the following steps:

[0052] The components are mixed uniformly, extruded and granulated at 200° C. to obtain a biodegradable polyester composition.

[0053] The obtained biodegradable polyester composition was put into a straw extruder, extruded at 180°C, cooled, and cut into straws. The specifications of the straws were fixed as follows: inner diameter: 11.2 mm, length: 230 mm, weight: 3 g, and tip angle: 40° to 65°.

[0054] Table 2 Component dosage in the examples and comparative examples (parts by weight)

[0055]

[0056] Performance Testing

[0057] The thickness, mechanical properties and heat resistance of the biodegradable polyester compositions prepared in Examples 1 to 10 and Comparative Examples 1 to 5 were measured using the following test methods:

[0058] Thickness measurement: Use a thickness gauge or vernier caliper to measure the thickness of at least 10 different places of the straw, and calculate the thickness range and relative deviation; thickness range δ = d max -d min , where δ is the thickness range, d max is the maximum thickness measured, d min is the minimum thickness measured. Relative deviation Rd = (dD) / D, where Rd is the relative deviation, d is the measured thickness, and D is the average value of the tested thickness.

[0059] Bending strength test: The bending strength test is carried out in accordance with the provisions of GB / T 9341-2008, with a test speed of 2 mm / min. The sample is prepared as a long strip sample of type B1 (80×10×4) mm.

[0060] Deformation temperature under load: It is carried out according to the B method of GB / T 1634.2-2004. The specimen is prepared as a long strip specimen of type B1 (80×10×4) mm.

[0061] The experimental results are shown in Tables 3-4.

[0062] Table 3 Performance test results

[0063] Group Thickness range (μm) Maximum relative deviation (%) Example 1 6 1.1 Example 2 4 0.3 Example 3 5 0.9 Example 4 6 1.2 Example 5 5 1 Example 6 6 1.2 Example 7 7 1.5 Example 8 5 1 Example 9 8 1.5 Example 10 6 1.4 Comparative Example 1 17 4 Comparative Example 2 13 5 Comparative Example 3 12 2 Comparative Example 4 8 3 Comparative Example 5 4 4

[0064] Table 4 Mechanical properties and heat resistance test results

[0065]

[0066]

[0067] It can be seen from the data in Table 3 that the biodegradable polyester composition prepared in the embodiment of the present invention has a lower thickness range and relative deviation, which can be explained that the biodegradable polyester composition prepared in the present invention can achieve higher stability during the extrusion process. At the same time, the biodegradable polyester composition prepared in the present invention also has good bending strength and heat resistance.

[0068] The melt flow rate of polybutylene succinate added in Comparative Example 1 is not appropriate, the residual monomer content of polylactic acid added in Comparative Example 2 is not appropriate, and the D50 particle size of the talc component added in Comparative Example 3 is not appropriate, resulting in large thickness deviation and relative deviation of the obtained biodegradable polyester composition, indicating that the interaction between polybutylene succinate with a specific melt flow rate, polylactic acid with a specific residual monomer content, and filler with a specific D50 particle size in the present invention can effectively improve the extrusion stability of the final biodegradable polyester composition. The weight fraction of the filler added in Comparative Examples 4 to 5 is not appropriate, and although the obtained biodegradable polyester composition has a smaller thickness deviation, its relative deviation is higher than that of the embodiment.

[0069] From the data in Table 4, it can be seen that the biodegradable polyester composition prepared in Example 2 of the present invention has good mechanical properties and heat resistance, and is better than the comparative example, wherein the bending strength can reach 2704 MPa, and the load deformation temperature can reach 83.2° C. This shows that the properties of the polybutylene succinate, polylactic acid, and filler components in the present invention not only affect the extrusion stability of the biodegradable polyester composition finally prepared, but also affect its mechanical properties and heat resistance.

[0070] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A biodegradable polyester composition, characterized in that The invention comprises the following components in parts by weight: 35-55 parts of polybutylene succinate, 25-45 parts of polylactic acid, and 10-30 parts of filler; The melt flow rate of the polybutylene succinate under the test conditions of 190° C. and 2.16 kg is 2 to 8 g / 10 min; The mass percentage of the residual monomer of the polylactic acid is ≤0.3%; The D50 particle size of the filler is ≤10 μm, and the filler includes at least one of calcium carbonate, talcum powder, bamboo powder, and straw powder; The straws made from the biodegradable polyester composition have a thickness range of <10 μm and a relative thickness deviation of <2%.

2. The biodegradable polyester composition according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 45-50 parts of polybutylene succinate, 30-40 parts of polylactic acid and 15-20 parts of filler.

3. The biodegradable polyester composition according to claim 1, characterized in that: The D50 particle size of the filler is 0.5-10 μm.

4. The biodegradable polyester composition according to claim 1, characterized in that: It also includes 0.2 to 2 parts of processing aids.

5. The biodegradable polyester composition according to claim 4, characterized in that: The processing aid includes at least one of a stabilizer, a lubricant, an antistatic agent, an antifogging agent, and a UV absorber; The stabilizer is at least one of tribasic lead sulfate, lead stearate, calcium stearate, zinc stearate, and magnesium stearate; the lubricant is at least one of stearamide, oleamide, erucamide, zinc stearate, a polymer composite ester of metal soap, ethylene bisstearamide, polyethylene wax, and a silicone lubricant; the antistatic agent is at least one of ethoxylated alkylamines, ethoxylated alkyl acid amines, and glycerol monostearate; the antifogging agent is at least one of glycerol esters, polyglycerol esters, sorbitan esters, ethoxylated nonylphenol, and ethoxylated alcohol; and the UV absorber is at least one of phenyl o-hydroxybenzoate, 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, and 2-hydroxy-4-n-octyloxybenzophenone.

6. A method for preparing a biodegradable polyester composition according to any one of claims 1 to 5, characterized in that: The following steps are involved: The components are mixed uniformly, extruded and granulated at 150-240° C. to obtain a biodegradable polyester composition.

7. Use of the biodegradable polyester composition according to any one of claims 1 to 5 in the manufacture of extruded products.

8. Use of the biodegradable polyester composition according to any one of claims 1 to 5 in the manufacture of straws.

Citation Information

Patent Citations

  • PBS (polybuthylenesuccinate) fully biodegradable material as well as preparation method and application thereof

    CN103709688A

  • Full-biodegradable material special for manicure and preparation method of full-biodegradable material

    CN114163796A

  • Composite toughened and high-temperature-resistant polylactic acid modified material and preparation method therefor

    WO2022252266A1